EFFECT OF DIPPING EGGS IN DIFFERENT CONCENTRATION OF ACETIC ACID ON THE INTERNAL AND EXTERNAL QUALITATIVE TRAITS OF EGGS - Chro Aziz; Shoxan Ali; Jaza Mohammed; Questan Ameen; Ahmed Shaker (Basrah Journal of Veterinary Research)
This study evaluated the effects of treating eggs with varying concentrations of acetic acid (0%, 5%, 10%, and 15%) on internal and external egg quality traits. A total of 40 fresh chicken eggs were divided equally among the four treatment groups. Eggs were immersed in their respective acetic acid solutions for 10 minutes, followed by rinsing and air-drying. Quality parameters, including weight, external dimensions, shell thickness, and internal traits, were measured before and after treatment. External traits such as egg breadth showed significant differences (P<0.05), with higher values observed at 5% and 10% concentrations, while egg length and shell thickness remained unaffected. Internal traits such as yolk and albumin weights were significantly influenced (P<0.05), with optimal values noted at 10% concentration. Egg volume and surface area also increased significantly with acetic acid treatments, particularly at higher concentrations (10% and 15%), while the shape index remained stable. Density-related traits such as egg and yolk density peaked at 10% and 5%, respectively, reflecting enhanced structural integrity and nutrient retention. The shell weight per surface area was highest at 5% concentration, suggesting improved calcium deposition. Overall, acetic acid concentrations of 5%-10% demonstrated the most favorable effects on egg traits, indicating the potential for moderate acid treatments to enhance certain quality parameters without compromising structural integrity. These findings provide valuable insights for optimizing acetic acid use in egg preservation and hatchery practices, warranting further research into extended exposure durations and alternative acids.